Benefits of mycorrhizal inoculation to ecological restoration depend on plant functional type, restoration context and time. (August 2019) - Neuenkamp, Lena; Prober, Suzanne M.; Price, Jodi N.; Zobel, Martin; Standish, Rachel J.
Abstract: Mycorrhizal inoculation can enhance outcomes of ecological restoration, but the benefits may be context-dependent. Here, we performed a meta-analysis of field studies to elucidate conditions in which adding mycorrhizal fungi enhances restoration success. We found inoculation increased plant biomass by an average effect size of 1.7 in 70 independent comparisons from 26 field-based studies, with the largest increases to N-fixing woody plants, C4-grasses and plants growing in soils with low plant-available P. Growth responses to inoculation increased with time for the first 3 yr after inoculation, especially for N-fixing woody plants and plants growing in severely altered soils. We found that mycorrhizal inoculation increased species richness of restored plant communities by 30%, promoted establishment of target species, and enhanced similarity of restored to reference communities. We conclude that the addition of mycorrhizal fungi to restoration sites can facilitate rapid establishment of vegetation cover, and restoration of diverse plant communities more akin to reference sites.